Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Motivasi Belajar Siswa Kelas X Pada Mata Pelajaran Informatika di SMK Negeri 2 Salatiga - Siska Ella; Krismiyati Krismiyati (Peneliti.net, 2023)
This study discusses the application of the Problem Based Learning (PBL) learning model in the Informatics subject at SMK Negeri 2 Salatiga with the aim of increasing student motivation. The research was conducted through a survey using Google Form to collect student responses to the use of the PBL model. The results showed that 95.6% of students gave positive responses to the PBL model, showing feelings of pleasure, interest, and high motivation, skills, activeness, discovery of new ideas, and understanding of the material. These findings indicate that the PBL model is effective in increasing student motivation. This model provides opportunities for students to be actively involved in solving problems that are relevant to real life, developing critical thinking skills, problem solving, and independent abilities. In addition, cooperation in groups and support from teachers and schools also have an important role in increasing student motivation. The results of this study conclude that the application of the PBL model in Informatics subjects can be an effective alternative to increase student motivation in various subjects Keywords: response questionnaire, learning motivation, student responses, Problem Based Learning